2013
DOI: 10.1016/j.chembiol.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Revertants, Low Temperature, and Correctors Reveal the Mechanism of F508del-CFTR Rescue by VX-809 and Suggest Multiple Agents for Full Correction

Abstract: Cystic fibrosis is mostly caused by the F508del mutation, which impairs CFTR protein from exiting the endoplasmic reticulum due to misfolding. VX-809 is a small molecule that rescues F508del-CFTR localization, which recently went into clinical trial but with unknown mechanism of action (MoA). Herein, we assessed if VX-809 is additive or synergistic with genetic revertants of F508del-CFTR, other correctors, and low temperature to determine its MoA. We explored and integrated those various agents in combined tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
186
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(208 citation statements)
references
References 54 publications
21
186
1
Order By: Relevance
“…7). Recent evidence shows that the correction of the F508del-CFTR trafficking defect by using VX-809 (Van Goor et al, 2011) has modest therapeutic efficacy (Clancy et al, 2012;Wainwright et al, 2015), suggesting that a combinatorial approach is needed to achieve correction levels that translate into clinical benefit (Amaral and Farinha, 2013;Farinha et al, 2013a). Our results show that the combined effect of VX-809 and 007-AM improves F508del-CFTR rescue relative to that of VX-809 alone by an additional 6% (from 11% to 17%).…”
Section: Discussionsupporting
confidence: 55%
“…7). Recent evidence shows that the correction of the F508del-CFTR trafficking defect by using VX-809 (Van Goor et al, 2011) has modest therapeutic efficacy (Clancy et al, 2012;Wainwright et al, 2015), suggesting that a combinatorial approach is needed to achieve correction levels that translate into clinical benefit (Amaral and Farinha, 2013;Farinha et al, 2013a). Our results show that the combined effect of VX-809 and 007-AM improves F508del-CFTR rescue relative to that of VX-809 alone by an additional 6% (from 11% to 17%).…”
Section: Discussionsupporting
confidence: 55%
“…Proteostasis regulators modulate the proteostasis environment, leading to beneficial effects on CFTR processing and plasma membrane stability (17). Regardless of their mechanism of action, the use of a single CFTR corrector is insufficient to achieve therapeutically relevant rescue of F508del-CFTR (19,20). Early studies of CFTR correctors identified a threshold in the maximal correction achieved with a single drug of about 20% wild-type (WT) CFTR function (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…One screen was performed using cells expressing ΔF508-CFTR in which the test compound was added together with VX-809, an established corrector that has been extensively characterized and is in clinical trials. Although the precise correction mechanism of VX-809 has not been resolved, current data suggest that VX-809 may target multiple sites at the NBD1-MSDs interface and interact with the N-terminal fragment of CFTR, represented by MSD1 or MSD1-NBD1 (Farinha et al, 2013;He et al, 2013;Loo et al, 2013; Okiyoneda et al, 2013;Ren et al, 2013). Mutagenesis studies and thermostabilization of ΔF508-CFTR suggest that VX-809 interacts directly with the channel (Okiyoneda et al, 2013), although indirect effects cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The idea for synergy screening is that global misfolding and dysfunction of ΔF508-CFTR can be efficiently reversed by stabilizing two major structural deficiencies (the NBD1 stability and the NBD-MSDs interfacial defects; Rabeh et al, 2012), which is supported by data from suppressor mutations and corrector combinations (Okiyoneda et al, 2013). Although VX-809 is unable to restore the thermal stability of the isolated ΔF508-NBD1 (Farinha et al, 2013;Okiyoneda et al, 2013;Ren et al, 2013), it is thought to directly stabilize the interface between NBD1 and MSDs (Van Goor et al, 2011;Farinha et al, 2013;Okiyoneda et al, 2013;Ren et al, 2013). Combining genetic modification (e.g., 3S suppressor mutation in the NBD1) of the ΔF508-NBD1 or chemical chaperones with VX-809 produced robust potentiation of the effect of VX-809 on the folding and cell surface expression of ΔF508-CFTR (Okiyoneda et al, 2013).…”
Section: Introductionmentioning
confidence: 98%